2017
DOI: 10.3201/eid2308.170029
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Laboratory Values as Early Indicators of Ebola Virus Infection in Nonhuman Primates

Abstract: The Ebola virus (EBOV) outbreak in West Africa during 2013–2016 demonstrated the need to improve Ebola virus disease (EVD) diagnostics and standards of care. This retrospective study compared laboratory values and clinical features of 3 nonhuman primate models of lethal EVD to assess associations with improved survival time. In addition, the study identified laboratory values useful as predictors of survival, surrogates for EBOV viral loads, and triggers for initiation of therapeutic interventions in these non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The finding that pathological evidence of pancreatitis was relatively rare (6%) in the rhesus IM EBOV-Kikwit model was not surprising, given our previous observations that significant biochemical evidence of pancreatitis, elevations of serum lipase, were not observed in three NHP IM models: EBOV-Kikwit or EBOV-Makona in rhesus macaques and EBOV-Kikwit in Cynomolgus macaques [ 21 ]. While some authors have reported hyperamylasemia in human EBOV in the past [ 29 ], it is entirely possible that the hyperamylasemia observed in human EBOV cases may not have been a marker for pancreatic injury but may have been either salivary in origin, a marker of intestinal injury, or renal failure [ 31 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The finding that pathological evidence of pancreatitis was relatively rare (6%) in the rhesus IM EBOV-Kikwit model was not surprising, given our previous observations that significant biochemical evidence of pancreatitis, elevations of serum lipase, were not observed in three NHP IM models: EBOV-Kikwit or EBOV-Makona in rhesus macaques and EBOV-Kikwit in Cynomolgus macaques [ 21 ]. While some authors have reported hyperamylasemia in human EBOV in the past [ 29 ], it is entirely possible that the hyperamylasemia observed in human EBOV cases may not have been a marker for pancreatic injury but may have been either salivary in origin, a marker of intestinal injury, or renal failure [ 31 ].…”
Section: Discussionmentioning
confidence: 91%
“…In the rhesus IM EBOV-Kikwit model, EBOV is believed to spread from the initial muscle infection site via antigen presenting cells (APCs)–monocytes, macrophages, and dendritic cells to regional lymph nodes, likely via lymphatics and the bloodstream and then rapidly disseminates throughout the entire host [ 20 ]. EBOV RNA is detectable as early as 3 DPI and peaks at 5–7 DPI [ 21 ]. In this model, we found that GALT is significantly affected in terminal disease, with pathological changes observed in animals that succumbed as early as 5 DPI.…”
Section: Discussionmentioning
confidence: 99%
“…These panels collectively provided results for 46 clinical laboratory parameters. Viral RNA copy numbers were determined using quantitative real-time PCR (qRT-PCR) [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…NHP models of EBOV infection have provided the most informative data related to the pathology and host response. In rhesus ( Macaca mulatta ) and cynomolgus ( Macaca fascicularis ) macaques infected with 1000 PFU of EBOV (intramuscular route), viremia is initially detected 3–4 days after infection, often coinciding with a febrile response [5, 6]. Monocytes/macrophages and dendritic cells are the first cell types that are infected; virus then spreads to the regional lymph nodes, liver and spleen by the movement of infected cells and free virus into the bloodstream.…”
Section: Introductionmentioning
confidence: 99%